2007
DOI: 10.2307/4125317
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Organization via a Facilitation Cascade in Intertidal Cordgrass Bed Communities

Abstract: It has recently been proposed that many communities are structured by a hierarchy of interactions in which facilitation by foundation species is of primary importance. We conducted the first explicit experimental test of this hypothesis by investigating the organization of positive interactions on New England cobblestone beaches. In this midintertidal community, wave-generated substrate instability and solar stress largely limit marine organisms to the shelter of cordgrass beds. Cordgrass, which can establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 0 publications
1
94
1
Order By: Relevance
“…Based on our observation that the most diverse and heavily invaded sites had cordgrass, and in accordance with recent conceptual and observational studies suggesting the potential importance of positive interactions for the correlated success of native and invasive species (Simberloff 1986, Levine and D'Antonio 1999, Richardson et al 2000, Stachowicz and Byrnes 2006, we conducted the following three experiments on the shores of the NB-NERR to test the hypothesis that a facilitation cascade (sensu Altieri et al 2007) in cordgrass beds enhances both native diversity and invader abundance, leading to their large-scale association.…”
Section: Study Systemmentioning
confidence: 99%
“…Based on our observation that the most diverse and heavily invaded sites had cordgrass, and in accordance with recent conceptual and observational studies suggesting the potential importance of positive interactions for the correlated success of native and invasive species (Simberloff 1986, Levine and D'Antonio 1999, Richardson et al 2000, Stachowicz and Byrnes 2006, we conducted the following three experiments on the shores of the NB-NERR to test the hypothesis that a facilitation cascade (sensu Altieri et al 2007) in cordgrass beds enhances both native diversity and invader abundance, leading to their large-scale association.…”
Section: Study Systemmentioning
confidence: 99%
“…flood protection, carbon and nutrient storage, biodiversity enhancement) [25][26][27][28]. In addition, these vegetated coastal ecosystems are globally disappearing [29,30], and costly restoration efforts, with various success rates, are being undertaken to halt and revert these losses.…”
Section: Introductionmentioning
confidence: 99%
“…Once Spartina alterniflora is established, its role as a foundation species and ecosystem engineer facilitates the establishment of plant communities behind (Bruno 2000) and invertebrate communities within (Altieri et al 2007) the bed. This successional development of the coastal environment ultimately climaxes in salt-marsh systems, unless harsh hydrodynamic conditions prevent the peat accumulation necessary for marsh development.…”
Section: Occurrence Of Coastal Habitats In Relation To Hydrodynamic Smentioning
confidence: 99%
“…In our study system, the hydrodynamic conditions along the environmental gradient effectively determine prevailing species interactions, which combine with positive feedbacks to generate distinct habitats from a common pool of potential component species. The shorelines are thus hierarchically organised (Altieri et al 2007), where environmental stress in the form of wave-driven substrate instability determines first where the foundation species S. alterniflora can establish, which in turn determines the nature of secondary interactions among the plants facilitated by S. alterniflora. Alternative hypotheses for variation in community type across the hydrodynamic gradient, such as seed dispersal, have been examined previously in our study system and have been shown not to limit distributions of shoreline forbs (Rand 2000, Bruno 2002.…”
Section: Occurrence Of Coastal Habitats In Relation To Hydrodynamic Smentioning
confidence: 99%